2023
DOI: 10.21608/niles.2023.279733
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies Among Elderly Women Suffering From Knee Osteoarthritis Pain At Beni-Suef City

Abstract: Background: Osteoarthritis (OA) is the main cause of pain and disability among elderly women. It is more common among female than male. Aim: This study aimed to assess the coping strategies of elderly women suffering from knee osteoarthritis (OA) pain in Beni-Suef city. Design: A descriptive cross-sectional research design was utilized in the current study. Setting: the study was carried out at Beni Suef university hospital in orthopedics outpatient clinic and the physiotherapy unit. Subjects: A non-probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The results of the current study showed that the majority of the studied women indicated that the OA disease had a significant negative impact on their social status when it came to the impact of OA on social health. These results may indicate that OA may contribute to limitations in involvement in social or professional settings, challenges with daily living tasks, and issues with gender, culture, family roles, and identities [37][38][39].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the current study showed that the majority of the studied women indicated that the OA disease had a significant negative impact on their social status when it came to the impact of OA on social health. These results may indicate that OA may contribute to limitations in involvement in social or professional settings, challenges with daily living tasks, and issues with gender, culture, family roles, and identities [37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…62 percent of people with OA are female. Men are more likely to have OA than women do after the age of 45 among those under 45 [1][2][3]. Knee osteoarthritis is either characterised as primary or secondary depending on the underlying aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss, cataracts and refractive errors, osteoarthritis and back and neck pain, chronic obstructive pulmonary disease, diabetes, depression and dementia are common illnesses among older adults. People are more prone to encounter multiple conditions concurrently as they get older [22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease, diabetes, depression, dementia, back and neck discomfort, cataracts, refractive errors, hearing loss and osteoarthritis are common illnesses in older adults. People are more prone to encounter multiple conditions concurrently as they get older [1][2][3][4]. Furthermore, some elders internalize the prevalent attitudes and views about aging in the larger culture.…”
Section: Introductionmentioning
confidence: 99%